A non-canonical phosphorylation site in β-casein A from non-Mediterranean water buffalo makes quantifiable the adulteration of Italian milk with foreign material by combined isoelectrofocusing-immunoblotting procedures. (30th March 2019) - Caira, Simonetta; Pinto, Gabriella; Nicolai, Maria Adalgisa; Novi, Gianfranco; Addeo, Francesco; Scaloni, Andrea
Highlights: Protected Denomination of Origin Mozzarella di Bufala Campana cheese has strict local characteristics. Italian and foreign water buffalo populations present differences in casein polymorphisms. Simple/fast isoelectrofocusing/immunoblotting procedures ascertained milk adulteration. αs1-CNdel-7P, β-CN A-6P and nicked β-CN A-5P were used as adulteration markers. Abstract: The need of controlling illegal addition of water buffalo (WB) milk from foreign countries to the Italian counterpart devoted to the production of Protected Denomination of Origin (PDO) Mozzarella di Bufala Campana (MBC) cheese has promoted the development of simple, fast and cheap isoelectrofocusing (IEF) methods for evaluating the nature of the raw material to be used according to a high-throughput sample multiplexing format, avoiding the use of dedicated mass spectrometry-based procedures. Thus, combined proteomic methods were here integrated with optimized western blotting protocols in solving the complex IEF pattern of casein (CN) mixtures observed when Italian and foreign WB milk are mixed together. Identification of internally deleted αs1 -CN hepta-phosphorylated species as well as of still unknown β-CN A hexa-phosphorylated and N-terminally-nicked β-CN A phosphorylated forms present uniquely in foreign WB milk samples, allowed recognizing these molecules as adulteration markers to be assayed in combined IEF-immunoblotting procedures; the latter ones showing optimal migration characteristics to be used in routine assays. A linear relationship between detected area of specific immunorecognized gel bands and percentage of international WB milk added to the Italian counterpart was verified, demonstrating that this method has an adulteration detection limit close to 3% v/v. Based on these results, this analytical procedure is here proposed as optimal one for evaluating the authenticity of PDO MBC cheese products.